RK* $$ R_{K^{\left(*\right)}} $$ and the origin of Yukawa couplings - Stephen F. King (Journal of High Energy Physics, 2018)
Abstract We explore the possibility that the semi-leptonic B decay ratios RK* $$ R_{K^{\left(*\right)}} $$ which violate μ − e universality are related to the origin of the fermion Yukawa couplings in the Standard Model. Some time ago, a vector-like fourth family (without a Z′) was used to generate fermion mass hierarchies and mixing patterns without introducing any family symmetry. Recently the idea of inducing flavourful Z′ couplings via mixing with a vector-like fourth family which carries gauged U(1)′ charges has been proposed as a simple way of producing controlled flavour universality violation while elegantly cancelling anomalies. We show that the fusion of these two ideas provides a nice connection between RK* $$ R_{K^{\left(*\right)}} $$ and the origin of Yukawa couplings in the quark sector. However the lepton sector requires some tuning of Yukawa couplings to obtain the desired coupling of Z′ to muons.